Maxillomandibular relationship record for implant complete mouth rehabilitation with elastomeric material and facial surface index of existing denture - Pravinkumar G Patil; Smita Nimbalkar-Patil (Wolters Kluwer Medknow Publications, 2015)
Introduction: The maxillomandibular relationship (MMR) record is a critical step to establish the new occlusion in implant supported complete mouth rehabilitation. Using patients existing denture for recording the MMR requires implant definitive cast to be modified extensively to completely seat the denture (with unaltered flanges) on it. This may influence the correct seating of the denture on the implant definitive cast causing faulty recording of the MMR. Materials and Method: Elastomeric record bases, reinforced with the resin framework, are fabricated and relined with the light body elastomeric material when all the healing abutments are in place. The MMR is recorded with these elastomeric record bases using vacuum formed facial surface index of the occluded existing dentures as a guideline. Results: The elastomeric record bases with facial surface index of the existing dentures can allow clinicians to record MMR records without removing the healing abutments from the mouth with acceptable accuracy. This can save chair-side time of the procedure. The record of facial surfaces of existing complete denture in the form of vacuum formed sheet helps to set the occlusal vertical dimension. Conclusion: Use of facial surface index together with the elastomeric record bases can be the useful alternative technique to record the MMR in patients with implant supported full mouth rehabilitation. Further study is required to prove its routine clinical utility.